2021
DOI: 10.51470/plantarchives.2021.v21.no1.122
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phytochemicals Isolated From Cucurbita Pepo Seeds Using Uv–vis and Ftir Spectroscopy

Abstract: CHARACTERIZATION OF PHYTOCHEMICALS ISOLATED FROM CUCURBITA PEPO SEEDS USING UV–VIS AND FTIR SPECTROSCOPY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
0
1
1
Order By: Relevance
“…Presence of phenol was observed in the peak at 3332.36 cm -1 [31], 3364.58 cm -1 [7], 3270 -3320 cm -1 [43], 3406.43 cm -1 [3]. But in the present study the phenol was found in 1375.40 cm -1 in the gametophyte extract of A. schimperiana subsp.…”
Section: Discussioncontrasting
confidence: 59%
“…Presence of phenol was observed in the peak at 3332.36 cm -1 [31], 3364.58 cm -1 [7], 3270 -3320 cm -1 [43], 3406.43 cm -1 [3]. But in the present study the phenol was found in 1375.40 cm -1 in the gametophyte extract of A. schimperiana subsp.…”
Section: Discussioncontrasting
confidence: 59%
“…Spektrofotometri UV-Vis dapat mengidentifikasi jenis senyawa dengan gugus kromofor dan mempunyai ikatan rangkap terkonjugasi. Selain itu, berbagai faktor seperti pH, komposisi larutan, suhu, keberadaan zat pengganggu atau pengotor, dan kebersihan kuvet yang digunakan dalam analisis dapat secara signifikan mempengaruhi hasil pengukuran penyerapan (Kambira et al, 2020;Rawat & Garg, 2021).…”
Section: Spektrofotometri Uv-visunclassified